Krytyczna teoria rasy (Critical Race Theory) i obecność koncepcji rasy w kontekscie przeszłych i bieżących amerykańskich dyskusji edukacyjnych - Drozdowicz, Jarema (Kultura-Społeczeństwo-Edukacja, 2012)
The concept of race seems to be, despite the efforts of various political movements of 1960’s still present in the public life and education in the Unites States. Contemporary educational debates in America in most cases tackle this problem through the lenses of a specific research approach which takes the concept of race as granted, when examining social relations in the American society. This approach, generally called Critical Race Theory (CRT) had been established in the late 1980’s, but its theoretical, methodological and political roots go back to the decade of the Vietnam War and the assassination of Martin Luther King or even further. This paper makes an attempt to deliver a closer look at the CRT and to highlight its most important assumptions and forms of political actions undertaken within the common frame of the racial concept. The Boasian tradition in the American way of conceptualization of race is an important factor in this debate. The past and present educational debates in the USA prove the fact that the idea of race is undergoing nowadays an intensive shift from its biological basis towards economic and social differences making the new conflicts even more visible in the American political landscape today.